2017
DOI: 10.1016/j.adaj.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of dental antibiotic prescribing practices in the United States

Abstract: Background Antibiotic prescribing practices among dentists and dental specialists in the United States (US) remains poorly understood. The purpose of our study is to compare prescribing practices between dental specialties, evaluate the duration of antibiotics prescribed by dentists, and determine variation in antibiotic selection among dentists. Methods We performed a retrospective cross-sectional analysis of dental provider specialties linked to de-identified antibiotic claims data from a large pharmacy be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
95
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 26 publications
10
95
1
Order By: Relevance
“…Although ADA guidelines no longer recommend erythromycin as the first choice for this clinical condition in four Polish universities, 1%-2% students recommended this antibiotic. 25 Proper treatment in a patient allergic to penicillins, which are often the first-line drugs in dentistry, was also addressed in our study. About 60% of graduating students suggested doxycycline or metronidazole, as a proper treatment for patients with aggressive periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ADA guidelines no longer recommend erythromycin as the first choice for this clinical condition in four Polish universities, 1%-2% students recommended this antibiotic. 25 Proper treatment in a patient allergic to penicillins, which are often the first-line drugs in dentistry, was also addressed in our study. About 60% of graduating students suggested doxycycline or metronidazole, as a proper treatment for patients with aggressive periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recent data have pointed at an increased risk of development of several diseases when antibiotics are given in the early stage of life. 25 It has been shown that antibiotics used early in life may produce deleterious effects on the microbiome with distant health consequences and may contribute to the emergence of antibiotic resistance. 27 This is the reason why their prescription should be limited to situations in which they are indispensable and include only a limited selection of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…With an aging population and with the number of patients with prosthetic joints increasing, recommendations for antibiotic prophylaxis (AP) in this specific population has generated significant discussion. However, little is known regarding the actual prescribing practices of dental providers . In addition, research evaluating satisfaction and adherence to professional guidelines might help in developing strategies to create awareness around such guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known regarding the actual prescribing practices of dental providers. 17,18 In addition, research evaluating satisfaction and adherence to professional guidelines might help in developing strategies to create awareness around such guidelines.…”
mentioning
confidence: 99%
“…4 Although urologists represented only 1.06% (9 210) of all prescribing providers in 2015, they were the eighth highest prescribers of outpatient antimicrobial agents among all specialties. 5 …”
Section: Introductionmentioning
confidence: 99%